2014
DOI: 10.1095/biolreprod.114.117564
|View full text |Cite
|
Sign up to set email alerts
|

Luteal Cells from Functional and Regressing Bovine Corpora Lutea Differentially Alter the Function of Gamma Delta T Cells1

Abstract: The luteal microenvironment is thought to direct the function of resident immune cells to facilitate either luteal function or regression. To determine if luteal cells from functional (Days 10-12) and regressing (8 h after administration of prostaglandin F2alpha) corpora lutea (CL) induce different responses in γδ T cells, luteal cells were cocultured with autologous γδ T cells isolated from peripheral blood. Proliferation, functional phenotypes, and cytokine synthesis were analyzed by flow cytometry. To deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…In cows, the CL is represented by granulose-luteal cells of large size and by small theka-luteal cells. Thekaluteal cells are located mainly peripherally; they penetrate the thickness of the CL together with connective tissue trabeculae (Cools et al, 2013b;Walusimbi and Pate, 2014;Xavier et al, 2012). In cows, luteal cells of "average size" are described; they are allocated to a special class with significant morphofunctional features.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In cows, the CL is represented by granulose-luteal cells of large size and by small theka-luteal cells. Thekaluteal cells are located mainly peripherally; they penetrate the thickness of the CL together with connective tissue trabeculae (Cools et al, 2013b;Walusimbi and Pate, 2014;Xavier et al, 2012). In cows, luteal cells of "average size" are described; they are allocated to a special class with significant morphofunctional features.…”
Section: Discussionmentioning
confidence: 99%
“…For many years, the morphology and function of bovine ovarian lutein structures have been the subject of intense research and discussion (Costa et al, 2020;Mogheiseh et al, 2020;Walusimbi and Pate, 2014;Xavier et al, 2012). The cellular composition of the CL has not been definitively determined (Fields and Fields, 1996;Fields et al, 1992;Parkinson et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Luteal steroidogenic cells are potent activators of T cells (18), the luteal microenvironment programs resident T cells (48, 49), and alteration in activation state of luteal T cells has been implicated in both luteal regression (50) and luteal rescue (19). Pathway analysis using IPA indicated that four differentially abundant lipids, including 5-KETE and 5,15-DiHETE, and two endocannabinoids, anandamide and 2-arachidonyl-glycerol may regulate activation of leukocytes.…”
Section: Discussionmentioning
confidence: 99%